High-density lipoprotein cholesterol and the risk of obstructive coronary artery disease beyond low-density lipoprotein cholesterol in non-diabetic individuals. (May 2020) - Kim, Yong-Giun; Cho, Young-Rak; Park, Gyung-Min; Won, Ki-Bum; Ann, Soe H; Yang, Dong H; Kang, Joon-Won; Lim, Tae-Hwan; Kim, Hong-Kyu; Choe, Jaewon; Lee, Seung-Whan; Kim, Young-Hak; et al.
Aims: The relationship between high-density lipoprotein cholesterol and the severity of coronary artery disease beyond low-density lipoprotein cholesterol, the primary target of cholesterol-lowering therapy, remains uncertain. We evaluated the association between high-density lipoprotein cholesterol and obstructive coronary artery disease using parameters of any obstructive plaque, obstructive plaque in the left main coronary artery or proximal left anterior descending artery, and obstructive plaque in multi-vessels, according to low-density lipoprotein cholesterol levels. Methods and results: We analyzed 5130 asymptomatic non-diabetics who underwent coronary computed tomography angiography for general health examination. Obstructive plaque was defined as a plaque with ≥50% luminal diameter stenosis. The participants were divided into three groups based on low-density lipoprotein cholesterol levels of ≤129, 130–159, and ≥160 mg/dl. The prevalence of any obstructive plaque (5.9% vs 6.4% vs 10.6%) and obstructive plaque in the left main coronary artery or proximal left anterior descending artery (2.1% vs 2.1% vs 4.3%) significantly increased with low-density lipoprotein cholesterol category (all p  < 0.05). Compared with subjects with high-density lipoprotein cholesterol level ≥40 mg/dl, those with high-density lipoprotein cholesterol level <40 mg/dl had a significantly higher prevalence of any obstructive plaque (10.4% vs 5.1%), obstructive plaque in the left main coronary artery or proximal left anterior descending artery (3.6% vs 1.8%), and obstructive plaque in multi-vessels (4.3% vs 1.1%), only in the group with low-density lipoprotein cholesterol level ≤129 mg/dl (all p  < 0.05). Multiple regression analysis showed that increased high-density lipoprotein cholesterol levels were associated with a reduced risk of all obstructive coronary artery disease parameters only in the group with low-density lipoprotein cholesterol level ≤129 mg/dl (all p  < 0.05). Conclusion: Increased high-density lipoprotein cholesterol levels were independently associated with a lower risk of obstructive coronary artery disease in asymptomatic non-diabetics with low low-density lipoprotein cholesterol levels.